Analysis of Factors Affecting Handover Quality in Nurses - Honan Honan; Muh. Abdurrouf; Dwi Heppy Rochmawati; Dyah Wiji Puspita Sari (GLOBAL HEALTH SCIENCE GROUP, 2025)
As many as 50% of adverse events in hospitals occur during the handover of patient information. There are several things that can affect handover quality, including knowledge, motivation, resources, peer support and supervision from the head of the room. The purpose of this study was to determine the factors of knowledge, motivation and supervision that affect the quality of handover in nurses at Sari Asih Serang Hospital. This research is quantitative, the type of survey research approach used is cross sectional. The sample in this study was collected from a population of 135 inpatient nurses at Sari Asih Serang Hospital. The number of samples was determined using the Slovin formula, obtained a sample of 101 nurses selected using purposive sampling technique, deliberate selection of samples based on criteria relevant to the research objectives. inclusion criteria include nurses who are willing to become respondents, aged 21-55 years, and work in the inpatient room. While the exclusion criteria were nurses who resigned, were absent due to illness, leave, or other reasons during the study. The multivariate analysis test used is multiple logistic regression. It is known that the supervision variable is confounding. There is a significant relationship between motivation and handover quality in nurses at Sari Asih Serang Hospital with a p value of 0.015 (p <  0.05) and there is a significant relationship between supervision and handover quality in nurses at Sari Asih Serang Hospital with a p value of 0.016 (p <  0.05). The most dominant variable affecting handover quality is knowledge with an OR of 3.993 after being controlled by supervision of the head of the room.